Unexpected Toxicology Findings in Rats Dosed With an Antihuman IL-13 Monoclonal Antibody. (September 2015) - Martin, Pauline L.; Nnane, Ivo P.; Branigan, Patrick; Louden, Calvert
Interleukin 13 (IL-13) is a type 2 helper T cytokine involved in allergic inflammation and immune responses to parasites. CNTO5825 is an antihuman IL-13 monoclonal antibody that inhibits the pharmacological activity of human, cynomolgus monkey, and rat IL-13. Repeated dose toxicology studies of 1- to 6-month duration were conducted in both rats and monkeys at doses of 20 to 100 mg/kg/wk. A decrease in the T cell-dependent antibody response to Keyhole Limpet Hemocyanin immunization was observed in monkeys but not in rats. In the 6-month rat study, there was a 2.2-fold increase in eosinophils in males at 3 and 6 months that was reversible. At necropsy (main and 4-month recovery), rats from control and CNTO5825-dosed groups were found to have pin worms, which may have contributed to the elevations in eosinophil. Testicular toxicity (dilatation of seminiferous tubules, atrophy, and degeneration of the germinal epithelium) was observed in 2 rats at 20 mg/kg and in 5 rats at 100 mg/kg (main and recovery). Brain lesions (unilateral focal accumulation of cells in the white matter of the cerebral cortex) were observed in 2 rats at 100 mg/kg, and vascular neoplasms (1 fatal multicentric hemangiosarcoma and 1 benign hemangioma) were observed at 100 mg/kg/wk. Overall, these studies show that CNTO5825 was without toxicity when administered to rats for up to 6 weeks and to monkeys for up to 6 months. However, when administered to rats for 6 months, a number of seemingly unrelated events occurred that could not be clearly linked to CNTO5825 administration, inhibition of IL-13, or to the immunological status of the animals.